2021
DOI: 10.1186/s12931-021-01698-9
|View full text |Cite
|
Sign up to set email alerts
|

Adhatoda Vasica attenuates inflammatory and hypoxic responses in preclinical mouse models: potential for repurposing in COVID-19-like conditions

Abstract: Background COVID-19 pneumonia has been associated with severe acute hypoxia, sepsis-like states, thrombosis and chronic sequelae including persisting hypoxia and fibrosis. The molecular hypoxia response pathway has been associated with such pathologies and our recent observations on anti-hypoxic and anti-inflammatory effects of whole aqueous extract of Adhatoda Vasica (AV) prompted us to explore its effects on relevant preclinical mouse models. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Adhatoda Vasica (100µg/ml) treatment also reduced the viral load in Vero cells infected with SARS-CoV-2 by 63%. [60] Trans membrane protease serine type 2 (TMPRSS2) is responsible for the priming of the viral S-protein to enter into the human alveolar epithelial cells. An in vitro study revealed the inhibition of protease TMPRSS2 by bromhexine hydrochloride, one of the derivatives of alkaloid vasicinone of Adhatoda vasica plant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhatoda Vasica (100µg/ml) treatment also reduced the viral load in Vero cells infected with SARS-CoV-2 by 63%. [60] Trans membrane protease serine type 2 (TMPRSS2) is responsible for the priming of the viral S-protein to enter into the human alveolar epithelial cells. An in vitro study revealed the inhibition of protease TMPRSS2 by bromhexine hydrochloride, one of the derivatives of alkaloid vasicinone of Adhatoda vasica plant.…”
Section: Resultsmentioning
confidence: 99%
“…[111] Vasa Kashaya (aqueous extract of Adhatoda vasica) in mouse (in vitro study) reduced the levels of transforming growth factor-β1 (TGF-β1), IL-6, Hypoxia inducible factor-1 α (HIF-1α) which are responsible for cytokine storm. [112] Vasicoline, Anisotine alkaloids inhibits main protease (Mpro) and RdRp (RNA-dependent RNA polymerase) of SARS-CoV-2 in molecular docking studies which shows their antiviral properties.…”
Section: Discussionmentioning
confidence: 99%
“…These include IL-17A, KC (murine IL-8 homologue) and hypoxia-inducible factor-1 (HIF-1) by restoring expression of its negative regulator—prolyl hydroxylase domain-2 (PHD2) (Gheware et al 2021b ). In vivo studies showed that increased transforming growth factor (TGF)-1, IL-6 and HIF-1 in pulmonary fibrosis and sepsis rescues siRNA-induced inflammation and modifies cellular hypoxic response and thrombosis (Gheware et al 2021a ). These studies figured out the potential role of A. vasica in inflammatory situations led in SARS-CoV-2 and suggest a possible role in severe steroid-resistant asthma.…”
Section: Antiviral and Immunomodulatory Activities Of Rasayana Herbsmentioning
confidence: 99%
“…for 8 days in male Wistar rats (methanolic, chloroform and diethyl ether extracts of leaves) Increase adhesion of neutrophils to nylon fibres Vinothapooshan and Sundar ( 2011 ) 130mg/kg for 21 days in male C57BL/6 mice (aqueous extract) Increases TGF-β1, IL-6, HIF-1α in pulmonary fibrosis and sepsis, rescues the siRNA-induced inflammation. Alters cellular hypoxic response, modulates thrombosis Gheware et al ( 2021a ) Asparagus racemosus Root aqueous extract (100mg/(kg b.w.p.o.) Balb/c mice Significant increase of CD3(+) and CD4/CD8(+) percentages, significant upregulation of Th1 (IL-2, IFN-γ) and Th2 (IL-4) cytokines suggesting its mixed Th1/Th2 adjuvant activity also showed higher antibody titres and DTH responses Gautam et al ( 2009 ) Phyllanthus amarus Schum.…”
Section: Antiviral and Immunomodulatory Activities Of Rasayana Herbsmentioning
confidence: 99%
“…[25] Vasa (Adhatoda vasica): a study tested the effect of whole aqueous extract of infected with SARS-CoV2. [26] Punarnava (Boerhavia diffusa): various studies suggest the immunomodulatory effect by Punarnava. [27.…”
Section: Stem Bark 2 Partmentioning
confidence: 99%